2012
DOI: 10.4103/2277-9175.100176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the administration of progesterone versus progesterone and vitamin D in improvement of outcomes in patients with traumatic brain injury: A randomized clinical trial with placebo group

Abstract: Background:Due to the heterogeneity of traumatic brain injury (TBI), many of single treatments have not been successful in prevention and cure of these kinds of injuries. The neuroprotective effect of progesterone drug on severe brain injuries has been identified, and recently, the neuroprotective effect of vitamin D has also been studied as the combination of these two drugs has shown better effects on animal samples in some studies. This study was conducted to examine the effect of vitamin D and progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…As alluded to earlier, rodent studies have suggested vitamin D together with progesterone has synergistic benefits. In agreement, patients administered intramuscular progesterone followed by vitamin D within 8 h of TBI had elevated recovery rates, GOS outcomes, and reduced mortality [118]. More positive studies are needed to fully warrant the use of progesterone.…”
Section: Progesterone Hyperosmolar Agents Decompressive Craniectomymentioning
confidence: 93%
“…As alluded to earlier, rodent studies have suggested vitamin D together with progesterone has synergistic benefits. In agreement, patients administered intramuscular progesterone followed by vitamin D within 8 h of TBI had elevated recovery rates, GOS outcomes, and reduced mortality [118]. More positive studies are needed to fully warrant the use of progesterone.…”
Section: Progesterone Hyperosmolar Agents Decompressive Craniectomymentioning
confidence: 93%
“…Omega-3 fatty acids may enhance brain repair and recovery, based on animal and clinical studies. 71 Similarly, vitamin D may offer neuroprotective and restorative benefits 72 in the acute TBI setting. In chronic TBI, vitamin D and omega-3 fatty acids may work synergistically, as they both may reduce neuroinflammation, apoptosis, and oxidative stress.…”
Section: Treatments For Tbimentioning
confidence: 99%
“…These seven studies, with 2492 total participants (Sample size, from 40 to 1179), compared progesterone with placebo in the treatment of acute TBI. Of these, only patients with severe TBI (Glasgow Coma Scale (GCS) ≤8) were included in five studies 8 9 10 11 12 , and in another 2 studies patients were recruited with moderate-to-severe TBI (GCS ≤12) 13 14 . All female patients were excluded in one included study 12 .…”
Section: Resultsmentioning
confidence: 99%